MICHAEL OHER’S PERSONALITY DEVELOPMENT IN MICHAEL LEWIS’S THE BLIND SIDE - Herni Lah; Mateus Rudi Supsiadji (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This study is about personality traits and personality development of the main character in The Blind Side by Michael Lewis. The research uses two theories to analyze. The first theory is big five theory by Robert McCrea and Paul Costa to analyze Michael Oher’s personality traits. The second theory is by Elizabeth B. Hurlock to analyze Personality developments which consist of eight determinants. The study uses a psychoanalytical approach and descriptive qualitative method to analyze the novel. The results of the analysis show that the main character in The Blind Side has several personality traits, along with the journey of his life, he experiences personality development, which changed from someone who was always alone, desperate, and hopeless slowly becoming someone who is confident, passion, enthusiasm to start his day and strong ambition for a better future.